ALOE-VERA GEL AS POTENTIAL CORROSION INHIBITOR FOR CONCRETE STEEL REINFORCEMENT - Héctor Herrera-Hernández (Avances en Ciencias e Ingeniería, 2015)
In this work a GEL extracted from ALOE VERA leaves has been electrochemically studied as a possible corrosion inhibitor for concrete steel rebar. The corrosion resistance was evaluated by Electrochemical Impedance Spectroscopy (EIS) measurements in hydrochloric acid solution (1M HCl) as a function of GEL-inhibitor addition, uninhibited measurements were also discussed. The impedance results revealed that after addition of different GEL-extract proportion, the corrosion process of the steel exposed to acidic solution is remarkably inhibited, and it was also determined that the molecules of the GEL-extract follow a physisorption mechanism on the metal surface according to the Langmuir isotherm model with and adsorption standard free energy of about G°ads 14.17 kJ/mol. In this sense, the GEL extracted from ALOE-VERA leaves behaved as a mixed-type inhibitor.